Studies on the Production of Protease by Bacillus Species - S. Ramesh, R. Nagalakshmi (Recent Research in Science and Technology, 2009)
The different bacterial isolates such as Bacillus subtilis, Bacillus coagulans, Bacillus firmus and mixed culture were screened for protease production.Ã‚Â A basal medium containing peptone, beef extract and NaCl was used for this biomass cultivation. Among the different bacterial isolates screened, the maximum protease production was found in B. coagulans and minimum in B. subtilis in both quantitative and semi quantitative assay. The effect of various environmental conditions like pH, temperature, rpm and inoculum size on alkaline protease production was examined.Ã‚Â The optimum condition for protease production upon inoculation of 1ml of overnight grown culture was found to be pH 9.2, 37Ã‚Âº C, 175 rpm and 1% of inoculum for a time period of 24 h.Ã‚Â One way analysis of variance showed significant differences (P < 0.05) in protease production between different species.